Renovación urbana en el centro histórico de la ciudad de Cartago por medio de la intervención del espacio público y sus actividades (2021)
This project addresses the problem of inadequate use and appropriation of public space by informal sellers, taking the historic center of the city of Cartago in the department of Valle del Cauca as the main point of this, based on this, is the need to find a way to provide an optimal use to these public spaces and in turn strengthen the dynamics of the area, This leads us to design an urban renewal project that improves the current conditions of informal sellers, creates adequate public spaces and strengthens the cultural vocation of the sector, through the creation of squares, facilities and green areas complemented with the use of artistic and cultural expressions; The use of an experimental design methodology together with applied research allows the collection of quantitative and qualitative data that justify this intervention demonstrating its feasibility and benefits for the city, resulting in the intervention of the Simon Bolivar Park and its surrounding pedestrian sideways, complementing and linking it with the dynamics of the area and providing a modern touch that contrasts with the historical of the city